Indonesian Exegetists and Multiculturalism: Study about Hamka and Muhammad Quraish Shihabs Idea on Multiculturalism - Syaik Abdillah; Ris’an Rusli (Islam Transformatif : Journal of Islamic Studies, 2023)
Abstract This article aims to discuss the idea of multiculturalism from the views of two Indonesian figures, Hamka and Quraish Shihab. Dawam Rahardjo (2010) argues that the principle of multiculturalism in Indonesia has not been properly understood because it is littered with mutual suspicion and concern, especially among majority and minority groups. In real terms, the idea of multiculturalism has not been received by Muslims in general. Firmly, the MUI and Kisdi (Indonesian Committee for Islamic World Solidarity) reject pluralism (2005); Multiculturalism as a pluralistic perspective is not only about recognizing and respecting the plurality of realities but also paying attention to aspects of interaction and the existence of each culture as equal entities. Based on the author's observations, the Qur'an contains many verses that can be used as a basis for building cooperation, mutual respect, tolerance and appreciation, a willingness to accept diversity, reconciliation between people, and peaceful coexistence between cultural groups, based on the principle of justice and equality,  and others multiculturalism principles. The methods used in this article are the content analysis method and the comparative method. Furthermore, this research uses historical and sociological approaches. Artikel ini bertujuan untuk membahas tentang gagasan multikulturalisme dari pandangan dua tokoh Indonesia, yaitu Hamka dan Quraish Shihab.  Dawam Rahardjo (2010), melihat bahwa prinsip multikulturalisme di Indonesia belum dipahami secara benar, karena dikotori oleh sikap saling curiga dan kekhawatiran, terutama kelompok mayoritas dan minoritas. Secara riel, gagasan tentang multikulturalisme belum mendapat penerimaan yang memadai dari umat Islam pada umumnya. Secara tegas, MUI dan Kisdi (Komite Indonesia untuk Solidaritas Dunia Islam) menolak paham pluralisme (2005); Multikulturalisme sebagai cara pandang kemajemukan bukan hanya sekedar mengakui dan menghormati kemajemukan realitas, tapi juga  memperhatikan aspek interaksi dan keberadaan setiap kebudayaan  sebagai entitas yang setara dan memiliki hak yang setara pula di tengah masyarakat. Berdasarkan pengamatan penulis, Al-Qur'an banyak memuat ayat yang bisa dijadikan asas untuk membangun kerjasama, saling menghormati, toleransi dan penghargaan, kesediaan untuk menerima keragaman, rekonsilidasi antarmanusia, dan hidup berdampingan secara damai antarkelompok budaya, berdasarkan prinsip keadilan, kesetaraan, dan prinsip multikulturalisme lainnya. Metode yang akan digunakan dalam penyusunan artikel ini adalah metode analisis isi (content analysis)dan metode komparatif. Lebih lanjut, penelitian ini menggunakan pendekatan historis dan sosiologis.